Aktivitas β-Glukosidase pada Beberapa Kelas Penggunaan Lahan Gambut Tropis di Pesisir Selatan, Sumatera Barat - nurul hijri; Mimien Harianti; Zuldadan Naspendra; Teguh Budi Prasetyo (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2022)
Most of the peatlands in Pesisir Selatan, West Sumatra have been converted into agricultural activities. Due to drainage, the peat decomposition process becomes faster. The activity of β-glucosidase is one of the enzymes that can be used as an indicator of the decomposition of organic matter and produces greenhouse gas emissions, likes CO2. Therefore, this study was conducted to identify the activity of β-glucosidase in several land uses in Pesisir Selatan peatlands. Observations were performed in several land-use types consisting of agricultural land (LP), bare land (LT), shrubs (SB), smallholder oil palm plantations (PSr), private company oil palm plantations (PSs), and forests (H). The activity of β-glucosidase was analyzed by using salicin and Na-acetate methods. The results of this study showed that the highest β-glucosidase activity was found in agricultural land use (LP). Based on the land use types, the activity of β-glucosidase follows agricultural land (LP) 3.42 μg.g-1.jam-1 > bare land (LT) 2.26 μg.g-1.jam-1 > shrubs (SB) 1.63 μg.g-1.jam-1 > smallholder oil palm plantations (PSR) 1.31 μg.g-1.jam-1 > private company oil palm plantations (PSs) 1.28 μg.g-1.jam-1 > forest (H) 0.80 μg.g-1.jam-1. Soil characteristic that significantly affects enzyme activity is water content where the higher the water content, the lower the β-glucosidase activity, and vice versa. Based on this study can be concluded that the change in land use from natural land to agricultural land triggers an increase in the activity of enzymes in decomposed peat materials.Key words: β-glucosidase, enzyme, palm plantation, land-use, peatland